The role of role models: In order for golf to really boom, youngsters need role models they can be inspired by and emulate - Muslim, Mohd Rom (2015)
Malaysian golf needs more young people to be interested and involved.There are lots of junior programmers being conducted at schools and clubs in the country, junior competitions are held regularly and golf clubs are becoming more accessible to juniors. The bottom line is this must continue to grow and attract the next generation of golfers.It is crucial to the long-term prosperity of the game.